Effect of sucrose and benomyl on in vitro multiplication of apple - Flores, Rejane; Lessa, Antonio Oliveira; Peters, José Antonio; Fortes, Gerson Renan de Luces (Pesquisa Agropecuaria Brasileira, 1999)
The purpose of this work was to study the effect of sucrose and benomyl concentrations on in vitro multiplication of apple (Malus prunifolia Willd, Borkh). The culture media composition was MS basal media plus 1 mg L-1 of BAP. Benomyl was harmful to M. prunifolia at all concentrations. The best sucrose concentrations was 30-45 g L-1, evaluated by shoot and bud number. The sucrose concentration of 45 g L-1 gave the biggest shoot length. The best shoot color was obtained at 15-30 g L-1 of sucrose.